Role of NS1 antibodies in the pathogenesis of acute secondary dengue infection - Jayathilaka, D; Gomes, L; Jeewandara, C; Jayarathna, G; Herath, D; Perera, P; Fernando, S; Wijewickrama, A; Hardman, C; Ogg, G; Malavige, G (Springer Nature, 2018)
The role of NS1-specific antibodies in the pathogenesis of dengue virus infection is poorly understood. Here we investigate the immunoglobulin responses of patients with dengue fever (DF) and dengue hemorrhagic fever (DHF) to NS1. Antibody responses to recombinant-NS1 are assessed in serum samples obtained throughout illness of patients with acute secondary DENV1 and DENV2 infection by ELISA. NS1 antibody titres are significantly higher in patients with DHF compared to those with DF for both serotypes, during the critical phaseof illness. Furthermore, both acute secondary DENV1 and DENV2 infection, the antibody repertoire of DF and DHF patients is directed towards distinct regions of the NS1 protein. In addition, healthy individuals, with past non-severe dengue infection have a similar antibody repertoire as those with mild acute infection (DF). Therefore, antibodies that target specific NS1 epitopes could predict disease severity and be of potential therapeutic benefit in aiding vaccine and treatment design.